The Influence of Funding Decisions, Institutional Ownership, and Current Ratio on Company Value with Return on Asset as a Moderator for Energy Sector Companies Listed on the Indonesian Stock Exchange - Rapita Pramanda; Fuad Ramdhan Ryanto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to analyze the influence of funding decisions, institutional ownership, and current ratio on company value, with return on assets (ROA) as a moderating variable, specifically in energy sector companies listed on the Indonesian Stock Exchange (IDX). The problem addressed is how these financial factors and ROA interact to affect the value of companies in the energy sector. The primary objectives of this study are to assess the impact of these variables on company value and to determine the moderating role of ROA. The research utilizes associative methods, with data collected from secondary sources, such as financial reports published by 52 energy sector companies on the IDX from 2021 to 2023. The data is analyzed using Moderated Regression Analysis (MRA), after conducting classical assumption tests including normality, multicollinearity, and heteroskedasticity. The findings indicate that funding decisions, institutional ownership, and current ratio significantly influence company value, and ROA moderates the relationship between these variables and company value. The results suggest that strategic decisions regarding funding, ownership structure, and liquidity management play crucial roles in enhancing company value, with ROA serving as a pivotal factor in strengthening these relationships.